LINEAR SINGULAR PERTURBATIONS OF HYPERBOLIC-PARABOLIC TYPE - Perjan, Andrei (Academia de Ştiinţe a Moldovei, 2003)
We study the behavior of solutions of the problem εu′′(t)+u′(t)+Au(t) =f (t), u(0) = u0, u′(0) = u1 in the Hilbert space H as ε → 0, where A is a linear,symmetric, strong positive operator.
Keywords: singular perturbations; parabolic equation; hyperbolic equation; boundary function